The Impact of Corporate Social Responsibility on Brand Sales: An Accountability Perspective - Nickerson, Dionne; Lowe, Michael; Pattabhiramaiah, Adithya; Sorescu, Alina (Journal of Marketing, 2022)
Consumers are increasingly mindful of corporate social responsibility (CSR) when making purchase and consumption decisions, but evidence of the impact of CSR initiatives on actual purchase decisions is lacking. This article introduces a novel brand accountability–based framework of consumer response to CSR initiatives, which categorizes CSR efforts as “corrective,” “compensating,” or “cultivating goodwill.” Leveraging a database of CSR press releases by leading consumer packaged goods brands, the authors examine the effect of the different types of CSR announcements on brand sales. The findings suggest that CSR initiatives that genuinely aim to reduce a brand's negative externalities (“corrective” and “compensating”) lift sales, whereas CSR actions focused on philanthropy (“cultivating goodwill”) can hurt sales. The authors propose two moderators—CSR reputation and CSR focus on environmental or social causes—and a mechanism for these effects, which they examine under controlled experimental settings. The experimental results show that, conditional on CSR reputation, consumers perceive varying degrees of sincerity in the different CSR types and that sincerity mediates the effect of CSR type on purchase intentions. Overall, the results suggest that consumers are more inclined to reward firms that directly reduce the negative by-products of their own business practices than to be impressed by public goodwill gestures.